Mixed feelings about supervisors the effect of LMX ambivalence on supervisor-directed behaviors - Chen, Lixin; Weng, Qingxiong; Popelnukha, Anastasiia; Jiang, Hui (2025)
Integrating norms of reciprocity, affect theory of social exchange, and ambivalence literature, we investigated how leader-member exchange (LMX) ambivalence influences employees’ interpersonal behaviors toward supervisors. Study 1, with a time-lagged field method, revealed that LMX ambivalence was positively related to both employee-rated supervisor-directed helping and deviant behaviors and that such relationships were mediated by emotional ambivalence toward supervisors. We also confirmed the amplification effects of workplace gossip about supervisors (WGS). Specifically, while receiving more positive WGS (PWGS) or less negative WGS (NWGS) could strengthen the positive relationship between emotional ambivalence and supervisor-directed helping behaviors, receiving less PWGS or more NWGS would accentuate the positive effect of emotional ambivalence on supervisor-directed deviant behaviors. Study 2 replicated our results with a scenario-based method and offered evidence for the mediating effect of emotional ambivalence toward supervisors. Study 3 included supervisor-rated helping and deviant behavior and a subjective measure of emotional ambivalence and again confirmed the mediating role of emotional ambivalence. Our findings extend knowledge of the interpersonal consequences of LMX ambivalence.
Keywords: Attitudes; Deviance; Deviant Behavior; Emotional Development; Emotional ambivalence; Helping behavior; Industrial Psychology; LMX ambivalence; Leadership Psychology; Social Psychology; Workplace gossip; Aufsatz in Zeitschrift